The enhanced model of hyperledger composer supply chain (hcsc) for the product environmental in supply chain networks - Arwa Mukhtar, Makki Kanani (2022)
Blockchain technology has received growing attention over the years. Recently, many blockchain-based models have been proposed to improve the issues of poor visibility in supply chains. However, due to the expansions and complexity in the operations of supply chains in the last few years, poor visibility is still one of the major challenges that lower the performance of supply chains. Besides, the existing blockchain models have key limitations in the common visibility measurements properties (VMP): information sharing, traceability, and inventory visibility such as a lack of identifying products based on environmental attributes to identify the green products. Still, there is a need to eliminate the time consumption in the current traceability systems. Current models share basic inventory information including inventory level and demand forecasts. Model HCSC is one of the important blockchain-based models that addressed information sharing and traceability; however, it lacks a feature of identifying product environmental attributes to know the green products, lacks a fast batch tracking of product storage temperature and expired products, and lacks visibility of inventory with less inventory cost by modelling safety stock and reorder points. Thus, this study proposes a Hyperledger composer supply chain products orders Stock (HCSC-POS) model based on the HCSC model to share product environmental sustainability attributes to the blockchain network in the identification of green products to control the environmental impact of production and improve the environmental sustainability. The proposed model enhances traceability by fast batch tracking of the product storage temperature and expired products for fast identification and recalling defective orders to reduce time consumption in product recalls. Additionally, it enhances the visibility of inventory with less cost by modelling safety stock and reorder points. The development of the proposed model consists of three main steps: 1-Extending the HCSC data model, 2- Developing the enhancements of the Blockchain Hyperledger Composer framework, and 3-Testing the proposed enhancements in the Hyperledger Composer execution runtime environment. To evaluate the proposed model, experimental test scenarios were conducted to evaluate traceability and inventory visibility enhancements in terms of time effectiveness and efficiency using real industry data from the manufacturing industry. The results show accessibility and availability of product environmental sustainability attributes with “environmentally friendly product” labels in the blockchain network. The model enhances the traceability of batches with less consumption time of about 89.47% better than other existing models in time responsiveness. In the inventory visibility, model HCSC-POS efficiency in terms of inventory costs showed about 60.48% reduction which was better than other models. These results offer the supply chain industry a competitive advantage in terms of environmental sustainability, fast batch traceability, and increased inventory visibility with less inventory cost by modelling safety stock and reorder points. This end-to-end visibility helps in the accurate business decision-making process and improves supply chain performance.